Effect of Moxidectin Treatment at Peripartum on Gastrointestinal Parasite Infections in Ewes Raised under Tropical Andes High Altitude Conditions - J. J. Vargas-Duarte; H. Lozano-Márquez; H. A. Grajales-Lombana; C. Manrique-Perdomo; D. A. Martínez-Bello; C. Saegerman; M. Raes; N. Kirschvink (Veterinary Medicine International)
This study tested the impact of moxidectin at peripartum on nematode fecal egg count (FEC) and clinical parameters on ewes in the high altitude tropical Andes of Colombia. FEC and clinical evaluations were performed on 9 occasions in 43 naturally infected ewes before and during gestation and after lambing. Moxidectin (Mox, 200 µg kg−1) was applied at late pregnancy (T1, n=15) or 48 hours after parturition (T2, n=14). 14 untreated ewes served as controls (C). Suckling lambs (n=58) remained untreated and underwent four clinical and parasitological evaluations until 8 weeks after birth. Mox efficacy equaled 99.3% (T1) and 96.9% (T2). Highest mean FEC value reflecting periparturient nematode egg rise (PPER) was recorded in C ewes at 4–6 weeks after lambing. Significant FEC reductions were found in T1 (94.8%) and T2 (96.7%) ewes (p<0.05). All lambs showed a significant and ewes-group independent increase in FEC before weaning (p<0.05). Clinical parameters (anemia and diarrhea) showed time- and treatment-related differences (p<0.05). Monitoring of FEC and clinical parameters linked to gastrointestinal parasite infections allowed demonstrating that postpartum or preweaning are two critical periods to nematode infection for sheep raised under tropical Andes high altitude conditions. Use of Mox as anthelmintic treatment prevented PPER.